Dirty, soothing, secret magic: individualism and spirituality in New Age and extreme metal music cultures. Issue 1 (3rd January 2019) - Coggins, Owen
Abstract: Taking inspiration from a press article comparing doom metal and New Age music, I explore individualism and magic in these musical cultures, reflecting on the 'dirty, soothing secret' suggested in that article's title. I trace the loosely defined characteristics of New Age music in the limited academic research on the topic, before situating the music in the wider New Age milieu which centres around the epistemological authority of the seeking self among diverse spiritual resources. Then, I examine the claims made about metal in the news article, drawing out themes which also relate to individualism and magic. Finally, I return to the concepts of the dirty, the soothing and the secret, arguing that these are not merely incidental aspects of the mainstream reception of New Age and metal music, but in fact can be understood as contributing to the magical potential of such music for listeners.